Sex- and Subtype-Related Differences of Personality Disorders (Axis II) and Personality Traits in Persistent ADHD. (December 2016) - Jacob, Christian P.; Gross-Lesch, Silke; Reichert, Susanne; Geissler, Julia; Jans, Thomas; Kittel-Schneider, Sarah; Nguyen, Trang T.; Romanos, Marcel; Reif, Andreas; Dempfle, Astrid; Lesch, Klaus-Peter
Objective: Despite growing awareness of adult ADHD and its comorbidity with personality disorders (PDs), little is known about sex- and subtype-related differences.Method: In all, 910 patients (452 females, 458 males) affected with persistent adult ADHD were assessed for comorbid PDs with the Structured Clinical Interview of DSM-IV and for personality traits with the revised NEO personality inventory, and the Tridimensional Personality Questionnaire.Results: The most prevalent PDs were narcissistic PD in males and histrionic PD in females. Affected females showed higher Neuroticism, Openness to Experience, and Agreeableness scores as well as Harm Avoidance and Reward Dependence scores. Narcissistic PD and antisocial PD have the highest prevalence in the H-type, while Borderline PD is more frequent in the C-type.Conclusion: Sex- and subtype-related differences in Axis II disorder comorbidity as well as impairment-modifying personality traits have to be taken into account in epidemiological studies of persistent ADHD.